Why Variation in Flower Color May Help Reproductive Success in the Endangered Australian Orchid Caladenia fulva - Basist, Georgia; Dyer, Adrian G.; Garcia, Jair E.; Raleigh, Ruth E.; Lawrie, Ann C. (Frontiers in Plant Science, 2021)
Caladenia fulva G.W. Carr (Tawny Spider-orchid) is a terrestrial Australian endangered orchid confined to contiguous reserves in open woodland in Victoria, Australia. Natural recruitment is poor and no confirmed pollinator has been observed in the last 30 years. Polymorphic variation in flower colour complicates plans for artificial pollination, seed collection and ex situ propagation for augmentation or re-introduction. DNA sequencing showed that there was no distinction among colour variants in the nuclear ribosomal internal transcribed spacer (ITS) region and the chloroplast trnT-trnF and matK regions. Also, authentic specimens of both C. fulva and C. reticulata from the reserves clustered along with these variants, suggesting free interbreeding. Artificial cross-pollination in situ and assessment of seed viability further suggested that no fertility barriers existed among colour variants. Natural fruit set was 15% of the population and was proportional to numbers of the different flower colours but varied with orchid patch within the population. Colour modelling on spectral data suggested that a hymenopteran pollinator could discriminate visually among colour variants. The similarity in fruiting success, however, suggests that flower colour polymorphism may avoid pollinator habituation to specific non-rewarding flower colours. The retention of large brightly coloured flowers suggests that C. fulva has maintained attractiveness to foraging insects rather than evolving to match a scarce unreliable hymenopteran sexual pollinator. These results suggest that C. fulva should be recognised as encompassing plants with these multiple flower colours, and artificial pollination should use all variants to conserve the biodiversity of the extant population.